The evolution of chemical defenses along invasion routes: Harmonia axyridis Pallas (Coccinellidae: Coleoptera) as a case study. Issue 16 (24th July 2018) - Magro, Alexandra; Ramon‐Portugal, Felipe; Facon, Benoît; Ducamp, Christine; Hemptinne, Jean‐Louis
Abstract: The evolution of increased competitive ability (EICA) hypothesis (Blossey & Nötzold, 1995 ) postulates that escaping from coevolved enemies increases invaders fitness by energy reallocation from defenses and immunity to growth and reproduction. In this context, we evaluated the evidence of evolutionary change in invasive populations of Harmonia axyridis Pallas (Coccinellidae: Coleoptera). We measured egg defenses—cocktail of hydrocarbons on the egg's surface flagging egg toxicity and the concentration of the main alkaloid harmonine—in individuals from three populations along the invasion route (Japan: native, United States: introduced more than 30 years ago, South Africa: introduced in the early 2000s) in a common garden experiment. Our results support the EICA hypothesis: We found changes along the invasion route in the profiles of the hydrocarbons coating the eggs' surface and a decrease in the concentration of harmonine in eggs from the most recent invasive South African population compared to the long established in the United States and the native Japanese ones. Abstract : The evolution of increased competitive ability (EICA) hypothesis postulates that escaping from coevolved enemies increases invaders fitness by energy reallocation from defenses and immunity to growth and reproduction. In this context, we evaluated the evidence of evolutionary changes in the chemical defenses of invasive populations of Harmonia axyridis Pallas (Coccinellidae: Coleoptera). Our results support the EICA hypothesis.